Patient safety incidents in the psychiatric inpatient setting: determinants, consequences, and strategies. A systematic review - Russotto, Sophia; Conti, Andrea; Masini, Alice; Tempia Valenta, Silvia; Vanhaecht, Kris; Mira, José Joaquin; Panella, Massimiliano (Frontiers in Psychiatry, 2026)
IntroductionPatient safety in psychiatric inpatient settings remains an underexplored area despite the heightened vulnerability of this population to preventable harm. This review aimed to provide an updated and comprehensive overview of Patient Safety Incidents (PSIs) in psychiatric inpatient settings, identifying their types, contributing factors, preventive strategies, consequences, and mitigating actions.MethodsA systematic search was conducted in PubMed, Embase and Scopus for primary studies published from 2000 onward. A total of 92 studies were included. Data were synthesized using the World Health Organization’s International Classification for Patient Safety as the guiding framework.ResultsThe most frequently reported PSIs included behavior-related incidents (self-harm, suicide attempts, and patient aggression), medication-related events, and patient falls. Contributing factors were predominantly linked to patient characteristics (e.g., psychiatric symptoms), staff performance and communication issues, organizational shortcomings (e.g., inadequate protocols), and environmental hazards (e.g., unsafe physical infrastructure). Preventive actions primarily focused on improving safety culture, staff training, and environmental modifications. However, only a minority of studies described intervention outcomes or reported quantitative data.ConclusionThis review highlights significant gaps in evidence-based interventions tailored to psychiatric care, as well as a lack of research from long-term care settings and low- and middle-income countries. To enhance patient safety in psychiatry, future efforts should prioritize the development and implementation of targeted strategies, multidisciplinary collaboration, integration with general patient safety initiatives, and robust quantitative evaluation. Strengthening safety culture across psychiatric facilities is essential to reduce harm and improve care quality for this high-risk population.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023389235.